Co-opetitive entrepreneurship : how to integrate competition in a co-operative context ? An empirical study of sami reindeer herders - Dana, Léo-Paul; Guieu, Gilles (Revue internationale P.M.E., 2014)
International audience Almost all research about co-opetition examines the emergence of co-operation in a competitive environment. Can competition emerge from a co-operative context ? While there is growing literature about indigenous entrepreneurship, this article focuses on competitive relationships among Sami people – the indigenous nation of northern Norway, Sweden and Finland and Russia’s Kola Peninsula. Reindeer herding, an activity traditionally done as a family, holds strong social value. Our ethnographic study reveals that maximisation of profits is not a sufficient explanatory variable to explain traditional reindeer herding. With limited economic returns from herding, many Sami herders rely on secondary occupations for supplementary income. To manage the resulting co-opetitive relationships, entrepreneurs compartmentalise co-operative relationships based on cultural and territorial issues, and competitive relationships based on economic considerations. Implications in terms of co-opetition and entrepreneurship are drawn. La casi totalidad de las investigaciones sobre coopetición se centra en elsurgimiento de la cooperación en un ambiente competitivo. ¿ Existen casos en que la competencia surge de un contexto cooperativo ? Una parte de la literatura en emprendimiento se interesa a un contexto específico del ejercicio del emprendimiento: el emprendimiento indígena. Es en el contexto específico del pueblo sami que abordamos el tema de las relaciones coopetitivas. Los sami son la población indígena del norte de la Escandinavia. Ellos viven actualmente en Noruega, Suecia, Finlandia y en la península rusa de Kola. El pastoreo de renos, actividad ejercida en un entorno familiar desde hace mucho tiempo, ha sido y sigue siendo un modo de vida con un alto valor social. Un estudio etnográfico realizado con los empresarios sami demuestra que el motivo del pastoreo es la preservación de la tradición, por encima dela maximización de los beneficios. Pues bien, hoy en día, ya que el pastoreo de renos es solo de ...